Simultaneous and ultra-sensitive detection of Cu2+ and Mg2+ in wine and beer based on dual DNA tweezers and entropy-driven three-dimensional DNA nanomachine. (1st October 2021) - Wu, Ge; Li, Yuting; Zhang, Jiafeng; Yun, Wen; Xiong, Zhengwei; Yang, Lizhu
Highlights: Simultaneous and ultra-sensitive detection strategy of Cu 2+ and Mg 2+ in wine and beer was developed. Three-dimensional DNA nanomachine was used for signal amplification. It has been successfully used to simultaneously detect of Cu 2+ and Mg 2+ in wine and beer. Abstract: Simultaneous and ultra-sensitive detection strategy of Cu 2+ and Mg 2+ in wine and beer was developed based on dual DNA tweezers and entropy-driven three-dimensional DNA nanomachine. The dual DNAzyme can simultaneously respond to two kinds of metal ions and cause two kinds of "turn-on" fluorescent signals. The working principle of this strategy was indirectly proven. In addition, some key experimental parameters were also optimized. Under the optimum conditions, the limit of detection was 10 pM for Cu 2+ and 2 nM for Mg 2+ respectively which was significantly improved by entropy driven amplification. This strategy also showed good selectivity and specificity. It was successfully used to detect of Cu 2+ and Mg 2+ in wine and beer with 5.26% to 9.12% of relative standard deviation and 90.4% to 110.5% of recoveries.